On the vertex covering sets and vertex cover polynomials of square of ladder graph. (3rd March 2016) - Vijayan, A.; Ida Helan, T. S.
Abstract: Let G be a graph of order n with no isolated vertex. A vertex covering of the graph G is a set of vertices such that every edge of the graph is incident to atleast one vertex of the set. Let C ( G, i ) be the family of vertex covering sets in G with cardinality ' i ' and let c ( G, i ) = | C ( G, i ) |. The polynomial is called the vertex cover polynomial of G . In this paper, we obtain some properties of vertex cover polynomials of . Also, we derive the reduction formula to calculate the vertex covering polynomials of .